Correlation between WOMAC score and hyalrunoic acid levels in knee osteoarthritis - Sharma, Nishant Raj; Singh, Sudhir; Kumar, Dharmendra; Kumar, Sanjiv (International Journal of Research in Medical Sciences, 2017)
Background: Osteoarthritis, a whole organ disease is diagnosed on clinical and radiological features, but plain radiographs show changes only in moderate to advanced stage of disease. Biochemical marker such as Hyaluronic Acid (HA) is used as a diagnostic tool in early stages. Hyaluronic acid level estimation has limited use in developing world due to cost and availability. Methods: A case-control study was done to correlate role of WOMAC score and serum Hyaluronic acid levels in knee osteoarthritis. All subjects were asked to fill the WOMAC questionnaire and were subjected to knee radiography. Blood samples of all subjects were tested for serum levels of Hyaluronic acid by Enzyme Linked Immuno-Sorbent Assay (ELISA). The assessment of severity was done by K-L grading of the radiographs. Results: The mean age in case group was 51.28 ± 7.93 years and in control group was 46.08 ± 4.81 years (P <0.001). A statistically significant difference in WOMAC score, HA levels and K-L grading of cases and controls was found (P <0.001). The results show a mild association of HA (r=0.421), moderate association of age (r=0.570), and strong association of K-L grade (r=0.910) with WOMAC scores and all these associations were highly significant (p<0.001). Multivariate analysis shows only WOMAC score >60 is independently associated with the outcome. Conclusion: WOMAC scores are significantly associated with knee osteoarthritis and can play a crucial role in identification, gradation and management of patients with knee osteoarthritis and can be used singly along with clinical features in situations where treatment cost and assessment of serum HA levels is of concern.